MSME Value Co-Creation Model in the Digital Gig Economy Ecosystem - Gautama Sastra Waskita; Denny Rakhmad Widi Ashari; Mohammad Basid Al Haris; Akhmad Rifa'i; Samlatul Izzah (ADI Bisnis Digital Interdisiplin Jurnal, 2026)
The rapid expansion of the gig economy has transformed collaborative practices among micro entrepreneurs, particularly within informal creative sectors in developing economies. However, existing studies largely focus on platform-based labor and formalized value co-creation, leaving the lived experiences of micro entrepreneurs in emerging creative hubs underexplored. This study aims to explore how micro entrepreneurs engage in value co-creation within Indonesia’s emerging creative ecosystems. Using a qualitative phenomenological approach, data were collected through in-depth interviews, participant observation, and document analysis involving 25 micro entrepreneurs from the F&B, barista, artisan, and creative sectors in Indonesian creative hubs. The findings reveal that value co-creation is deeply embedded in relational trust, community reciprocity, hybrid digital–community interaction, and identity formation. Co-creation practices were found to function not only as economic strategies but also as mechanisms for collective resilience, social belonging, and entrepreneurial legitimacy. The study extends the literature on Service-Dominant Logic and gig economy research by highlighting the socio-cultural and place-based dimensions of collaborative entrepreneurship in developing economies. Practically, the findings provide insights for policymakers, creative hub managers, and micro entrepreneurs in fostering sustainable and inclusive creative ecosystems.